2017
DOI: 10.1177/1078155217719585
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical assistance programs for cancer patients in the era of orally administered chemotherapeutics

Abstract: Introduction The rising cost of cancer drugs may make treatment unaffordable for some patients. Patients often rely on drug manufacturer-administered Pharmaceutical Assistance Programs (PAPs) to obtain drugs and reduced or no cost. The overall usage of PAPs within cancer care delivery is unknown. Methods We included all cancer patients across an academically affiliated, integrated health system in North Carolina during 2014 ( N = 8591). We identified the subset of patients receiving PAP assistance to afford on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 20 publications
(27 reference statements)
0
18
0
Order By: Relevance
“…Similar studies have found that these types of financial assistance programs can play a role in reducing out-of-pocket expenses for prescriptions drugs and OAMs. [9][10][11][12] Mitchell et al (2018) performed a similar study that evaluated the number of oncology patients receiving patient assistance programs for OAMs and the retail value of the assistance. 13 This study found that 10.6% of patients obtained a patient assistance program for an oral cancer medication, where our quality improvement project showed 18.6% of patients received a patient assistance program.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…Similar studies have found that these types of financial assistance programs can play a role in reducing out-of-pocket expenses for prescriptions drugs and OAMs. [9][10][11][12] Mitchell et al (2018) performed a similar study that evaluated the number of oncology patients receiving patient assistance programs for OAMs and the retail value of the assistance. 13 This study found that 10.6% of patients obtained a patient assistance program for an oral cancer medication, where our quality improvement project showed 18.6% of patients received a patient assistance program.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…10,17 In an earlier study by Zullig et al, 12 who investigated the use of PAPs for all anticancer medications dispensed by an academic oncology pharmacy, the median drug price was $2,762, and 12% of prescriptions were paid for with financial assistance. Similarly, Mitchell et al 11 reported on the use of PAP assistance among 10.6% of patients receiving any oral anticancer agents in a similar setting. In that study, 40% of recipients of charitable support were uninsured, and only 20% had Medicare coverage.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies indicated that approximately 10% to 15% of patients who received any cancer therapy used PAPs to offset out-of-pocket costs, but the extent of this support for the novel ultraexpensive anticancer agents has not been investigated. [10][11][12] Studies that directly assessed the use of PAPs concluded that they cover only a small percentage of total cancer drug costs, but they can facilitate access for underinsured individuals. [12][13][14] Our objective was to examine sources of payment for patients who have been prescribed novel oral anticancer agents by using data from an oncology specialty pharmacy that is linked to patients' clinical medical records and is affiliated with an academic cancer center.…”
Section: Introductionmentioning
confidence: 99%
“…Uninsured or self-pay individuals are generally responsible for the full cost of their care unless they are able to navigate the complex structure of safety net resources, including hospital charity care, entitlement programs, manufacturer assistance, and nonprofit organization aid. 17,18 Yet the literature is clear; no group, regardless of insurance type or generosity, is fully immune from individual-level financial burden of cancer. 2,12,19 It is also worth noting that cancer treatment may not follow standard economic models of choice.…”
Section: What Is Financial Toxicity?mentioning
confidence: 99%